Systematic approach to develop and validate High Performance Liquid Chromatographic method for efavirenz and its degradants - Sahoo, Sudhir Kumar; Choudhury, Prasanta Kumar; Murthy, P N; Mishra, Uma Shankar; Bisoyi, Saroj Kanta; Kumar , Lokesh (Journal of Applied Pharmaceutical Research, 2024)
Background: The crucial aspect to consider during method development and validation, ensuring accurate, precise, and specific estimation of drug substances and drug products, is stability. Various factors, including environmental, instrumental, reagent, and human factors, can pose challenges in achieving suitable method development and validation. Objective: This work aimed to develop and validate a low flow rate, LCMS compatible, simple, and rapid reverse-phase high-performance liquid chromatographic method for estimating efavirenz and its degradation products at different stress conditions. Materials and Methods: The HPLC system employed a Phenomenex Luna 5μ C18 (2) 100A (250 x 4.6 mm) column and a mobile phase of methanol: 20 millimolar ammonium formate solution (90:10) adjusted to pH 4 with formic acid. All analytes were separated within 15 minutes and detected at 247 nm. Method validation was carried out according to ICH guidelines, including linearity, accuracy, precision, ruggedness, robustness, LOD, and LOQ. Results and Discussion: The method was linear in the 10-90 μg/ml range, with a regression coefficient 0.999. Intra- and inter-day precisions, ruggedness, and robustness were within acceptable limits (≤2% RSD) with LOD and LOQ of 0.35 and 1.16 μg/ml, respectively. Degradation study indicates well resolution of the drug and degradants.  Conclusion: Purposeful degradation of efavirenz resulted in different degradation products under various stress conditions, and the method demonstrated satisfactory resolution from its degradants.